Pelatihan Hutan Wakaf dan Perhitungan Karbon di Desa Cibunian, Kecamatan Pamijahan, Kabupaten Bogor - Khalifah Muhamad Ali; Muhammad Alam Firmansyah; Nur Hasanah; Adelia; Chandra Kirana Shaleha; Haifa Salsabila Huda; Miftahul Jannah; Mu'minah Mustaqimah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Cibunian Village, Pamijahan District, Bogor Regency, has great potential as an ecotourism destination. One of the unique tourist destinations currently being developed is the Bogor Waqf Forest. However, this village is highly prone to landslides, requiring collaboration from various parties to address the issue. One of the potential collaborations is with the youth, through the Cibunian Village Youth Organization (Karang Taruna). This community service program aims to improve the knowledge and skills of the Cibunian Village Youth Organization (Karang Taruna) administrators regarding zakat waqf literacy, waqf-based forests, Waqf Forest applications, and carbon accounting. The entire series of activities was held in September 2024, in the form of four training sessions. The first two sessions are lectures by resource persons on zakat waqf literacy and waqf-based forests, and the final two sessions are practical carbon accounting for trees in the Bogor Waqf Forest and the use of the Waqf Forest application. The data collection method was through questionnaires before and after training, analyzed descriptively, as well as an assessment of direct practical activities during the training session. Based on observations, it can be concluded that the Cibunian Village Youth Organization (Karang Taruna) has improved their understanding of the basic concepts of zakat and waqf, as well as their ability to conduct surveys, operate the Waqf Forest application, perform carbon calculations, and manage waqf-based forests. This can enhance the sense of ownership and role of local communities in protecting the environment, preventing disasters, and optimizing village potential through waqf-based forests.